Půjčit si je tak snadno...: Půjčka v zastavárně z perspektivy finanční (ne)gramotnosti - Rádl, Michael (Lidé města, 2020)
In this article, I focus on the issue of the financial literacy of regular pawnshop customers. Generally, the terms of the pawn loan are considered as relatively unfavourable, so I was interested in the level of financial literacy of regular borrowers. During field research, it turned out that a pawn loan can be viewed from both the economic and a symbolic perspective. While the former is strictly rational and takes into account the costs and benefits with regard to the specific goals, the latter is rather related to the reasons that borrowers put forward at the moment they decide to accept the loan fee, and concerns such terms as self-esteem, prestige, or position in the social hierarchy. To the uninformed observer, a pawn loan may seem relatively irrational, and the ignorance of the context may make the impression that the financial literacy of those who borrow money in a pawnshop under quite unfavourable conditions is relatively low. However, this view of the issue is not complex, since it completely overlooks the situation and living conditions of borrowers. The question arises whether the commonly used concept of financial literacy is universally applicable to all strata of society, or whether disadvantaged groups in certain life situations act according to different principles of financial literacy, which are adapted to their given living conditions